Le Domaine. Une belle histoire qui se poursuit... Trois coopératives... Tout un début! - Desbiens, Josée; Pronovost, Claude (Les Services du Domaine Inc, 2003)
Keywords: Chaurès-Louard; Berthe; Coopérative d'habitation de Montréal; La Familiale; Logement

Pointe-à-Callière: le marché, façon XVIIIe - Labrosse, Francine (Continuité, 2003)
issued: 2003-23-00
Keywords: Marchés; Musée Pointe-à-Callière; Musées

L'Hôtel Rasco: inventaire et fouille archéologiques au site Le Royer (BjFj-53), 1998: Vieux-Montréal et faubourgs - Arkéos (Ville de Montréal, 2003)
Keywords: Archéologie; Hôtellerie

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

Terminus ferroviaires et espace urbain: le Canadien Pacifique et la transformation de l'est de Montréal, 1870-1915 - Duchesne, Julie (Université du Québec à Montréal, 2003)
Keywords: Canadien Pacifique; Chemins de fer

La librairie Rolland, 1842-1888 - Déry, Boris (Université du Québec à Montréal, 2003)
Keywords: Librairie

La transmission du patrimoine seigneurial des familles du gouvernement de Montréal aux XVIIe et XVIIIe siècles - Couvrette, Sébastien (Université de Montréal, 2003)
Keywords: Famille; Notaires; Seigneurie

Marchés publics et structuration spatiale du commerce à Montréal: 1870-1900 - Rousseau, Dany (Université du Québec à Montréal, 2003)
Keywords: Marchés

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment—despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

L'habitation type. Évolution de l'immeuble locatif pour les quartiers ouvriers: le cas de Verdun - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Logement; Quartiers; Verdun

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

Le syndicalisme dans le commerce de l’alimentation: le cas de la grève chez Steinberg en 1975 - Durand, Caroline (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2003)
issued: 2003-23-00
Keywords: Grèves; Steinberg; Épicerie

L'implantation de la galerie d'art à Montréal: le cas de W. Scott & sons, 1859-1914. Comment la révision du concept d'œuvre d'art autorisa la spécialisation du commerce d'art - Sicotte, Hélène (Université du Québec à Montréal, 2003)
Keywords: Expositions; Peinture

The Engineers' Engineer: Sir John Kennedy and the Port of Montreal - White, Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Ingénieurs; Port